OPTIMIZING ISLAMIC FINANCIAL MANAGEMENT STRATEGIES FOR SIGNIFICANT IMPACT ON PROFITABILITY: A STUDY ON MUSYARAKAH AND MURABAHAH FINANCING IN SHARIA BANKS - Nursyidah (RADJA PUBLIKA, 2022)
The purpose of this study is to identify the effect of murabaha and musyarakah financing on profitability in Bank Aceh Syariah. The research method used in the preparation of this final project is a quantitative research method, using a sample of Bank Aceh Syariah financial reports. The results of the study concluded that based on the t test, the musyarakah financing variable has a significant influence on ROA (Return on Assets), with musyarakah financing results of 2.3 million rupiah per month, so it can be concluded that there is a partial effect of the musyarakah variable on ROA of Bank Aceh Syariah . The murabahah financing variable also has a significant influence on ROA, with murabahah financing yields of 2.9 million rupiah per month, so it can be concluded that there is a partial effect of the murabahah variable on the ROA of Bank Aceh Syariah. The results of the F test show that the musyarakah and murabahah variables together have a significant effect on the ROA variable, with income reaching 5.4 million rupiah each month. Thus, based on the test of the coefficient of determination (R Square), the coefficient value of R Square is 0.247 or 24.7%, which indicates that an Islamic financial management strategy has the potential to have a significant impact on the profitability of Islamic Banks through musyarakah and murabahah financing.